Predicting variations to missed nursing care: a three-nation comparison - Blackman, Ian; Papastavrou, Evridiki; Palese, Alvisa; Vryonides, Stavros; Henderson, Julie; Willis, Eileen (My University, 2018)
Aims: To measure and model Australian, Cypriot and Italian nurses’ beliefs about what care is missed and how frequently it occurs within their settings. Background: This study expands on previous MISSCARE research but now applies and predicts missed care within three countries. Methods: Multivariate analysis was performed to estimate 1,896 nurses’ consensus scores about missed care activities based on Alfaro-Lefevre’s conceptual framework of care priorities. Results: Five latent variables have direct predictor effects on missed care frequencies. Another four variables including the nurses’ age, highest qualifications, absenteeism rate and workplace type, contributed to explaining the overall variance of missed care scores. The nurses’ gender had no influence on missed care. Conclusion: Cross country comparisons of missed nursing care allow for a more refined identification of strategies for remediation for both managers and clinicians. Implications for Nursing Management: Reliable consensus estimates about the types and frequencies of missed care can be scaled with variables identified to predict missed care across three different countries. Comparative international studies build on the foundations for understanding missed care in terms of nursing practices, policies and related social policies.
Keywords: Australia; Cyprus; Italy; Missed nursing; Multi-variate analysis